Modification of Waste Leather Trimming with in Situ Generated Silver Nanoparticles by One Step Method - Ashok, Basa; Umamahesh, Mallavarapu; Hariram, Natarajan; Siengchin, Suchart; Rajulu, Anumakonda Varada (Applied Science and Engineering Progress, 2021)
Waste leather trimming (WLT) was modified by in situ generation of silver nanoparticles (AgNPs) and silver oxide nanoparticles (Ag2ONPs) by one step thermal assisted method. The modified WLT was analyzed by FTIR, SEM, EDS, XRD and TGA techniques and antibacterial analysis. The generated silver based nanoparticles had a mean size of 93 nm. The FTIR spectra revealed no major changes between WLT and modified WLT. The XRD studies indicated additional peaks in the diffractogram of modified WLT which belonged to AgNPs and Ag2ONPs. The unmodified WLT had four inflection temperatures at 89, 303, 454, and 785°C while these values for the modified WLT were 84, 211, 305, and 328°C indicating a slight lowering of thermal stability due to the catalytic activity of the generated silver based nanoparticles. Further, the modified WLT formed the inhibition zones against E.coli, P.aeruinosa, S.aeureus and B.lichinomonas bacteria with diameters of 33, 36, 29, and 30 mm respectively. Hence, the modified WLT can be considered as filler for making low cost antibacterial biocomposites.